2016
DOI: 10.26491/mhwm/61735
|View full text |Cite
|
Sign up to set email alerts
|

Climate analysis as a basis for a sustainable water management at the Lusatian Neisse

Abstract: Abstract. current and future climate conditions and their impact on water balance, ecosystems, air quality and bioand agro-climatology were investigated in the region of the lusatian neisse within the two eu-projects -neyMO and klaPS. This work focuses on the climate analysis of the region at the german-Polish border as a preliminary step for a hydrological analysis of current and future conditions.Observed climatological data were processed and analysed using the indicators air temperature, precipitation, sun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Romanowicz et al (2016) used bias-adjusted modelled temperature and precipitation (seven GCM-RCM combinations from the EURO-CORDEX initiative over 10 Polish catchments) and found that projections following the RCP4.5 emission scenario agreed on a precipitation increase of up to 15 %, and a warming of up to 2 • C by the end of the 21st century. Pluntke et al (2016) applied a statistical downscaling model to produce temperature and precipitation projections from two global climate models following three different emission scenarios (RCP2.6, RCP8.5, and SRES A1B) for the southwest of Poland and eastern Saxony. They found an acceleration of changes by the end of the 21st century leading to negative consequences for the climatic water bal-ance, particularly under SRES A1B and RCP8.5 emission scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Romanowicz et al (2016) used bias-adjusted modelled temperature and precipitation (seven GCM-RCM combinations from the EURO-CORDEX initiative over 10 Polish catchments) and found that projections following the RCP4.5 emission scenario agreed on a precipitation increase of up to 15 %, and a warming of up to 2 • C by the end of the 21st century. Pluntke et al (2016) applied a statistical downscaling model to produce temperature and precipitation projections from two global climate models following three different emission scenarios (RCP2.6, RCP8.5, and SRES A1B) for the southwest of Poland and eastern Saxony. They found an acceleration of changes by the end of the 21st century leading to negative consequences for the climatic water bal-ance, particularly under SRES A1B and RCP8.5 emission scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…For the south-western part of Poland and eastern Saxony a similar increase, especially in the mountainous part, is accounted for by increased precipitation at altitudes of 350-650 m (Pluntke et al 2016).…”
Section: Discussionmentioning
confidence: 82%
“…An analysis of research papers on relationships between climate change and the runoff of mountain watersheds leads to conflicting conclusions (Sayemuzzaman, Manoj 2014;Pluntke et al 2016;Piniewski et al 2017;Szwejkowski et al 2017;Mangini et al 2018;Kohnová et al 2019). The fact is that the main climatic factors involved in the formation of river runoff are air temperature and precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, work on the drainage of the field is associated with drilling a large number of filtration wells, through which groundwater is pumped [2]. The complex of preparation works associated with the drainage of the deposit [3] has a direct effect on the state of the aquifers in the surface mining area [4].…”
mentioning
confidence: 99%